2017
DOI: 10.1097/01.nep.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

A Crisis in Competency: The Strategic and Ethical Imperative to Assessing New Graduate Nurses’ Clinical Reasoning

Abstract: New data suggest that we are losing ground in the quest for entry-level competency. Graduates often are underprepared to operate in the complex field of professional practice where increased patient acuity and decreased length of stay, coupled with a lack of deep learning in our academic nursing programs, have exacerbated a crisis in competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(149 citation statements)
references
References 9 publications
3
145
0
1
Order By: Relevance
“…But, as previously discussed, the dangers of a limited epistemological position have been articulated effectively and discussed in fields such as nursing, medical practitioners and teaching cf. [82][83][84]. Therefore, there is a need for exercise praxis to move beyond dichotomous assumptions of either/or in professional knowledge [85].…”
Section: Discussionmentioning
confidence: 99%
“…But, as previously discussed, the dangers of a limited epistemological position have been articulated effectively and discussed in fields such as nursing, medical practitioners and teaching cf. [82][83][84]. Therefore, there is a need for exercise praxis to move beyond dichotomous assumptions of either/or in professional knowledge [85].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing nursing students' clinical reasoning skills may improve their ability to recognize a deteriorating patient and therefore improve patient outcomes. Kavanagh and Szweda (2017) reviewed the results of the Performance Based Development System, a reliable and valid competency assessment system, and identified that 76-80% of more than 5,000 inexperienced nurses do not meet the clinical reasoning expectations for new nurses. No differences were found based on the new nurses' level of education (Kavanagh & Szweda, 2017).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…It is also reported by Missen et al () that while NGRNs perform adequately within their scope of practice in basic clinical skills, their advanced clinical skills remain an area of concern. Kavanagh and Szweda (, p. 57) assert that “…knowledge development in clinical practice requires experiential teaching and learning through facilitated, situated cognition with reflection…” a statement supporting Benner's () “novice to expert” model. This paper discusses the findings from the qualitative arm of a mixed methods study which explored new graduate registered nurses transition experiences particularly related to patient safety.…”
Section: Introductionmentioning
confidence: 99%